CONSTITUTIONAL THEORY AND THE DUTIES OF THE CONSTITUTIONAL COURT IN SAFEGUARDING CONSTITUTIONAL RIGHTS - Srikandi; Riyanto, Slamet (Penerbit Universitas Atma Jaya Yogyakarta, 2025)
The constitution serves as the highest legal norm and foundational framework for the governance of a sovereign state. Within the framework of constitutionalism, the constitution is understood not merely as a collection of written or unwritten rules, but as the embodiment of a normative hierarchy that guides state authority and ensures the protection of citizens’ rights. The Constitutional Court of the Republic of Indonesia plays a central role in upholding constitutional supremacy and safeguarding constitutional rights. Its powers include judicial review of legislation, constitutional interpretation, settlement of electoral disputes, adjudication of constitutional complaints, and—through specific legal procedures—issuing decisions on the dismissal of the President and/or Vice President. This article employs a normative juridical method with a qualitative approach, based on secondary data drawn from constitutional texts, legal literature, and decisions of the Constitutional Court. Through doctrinal analysis, the study reveals that the Constitutional Court functions not only as the guardian of the Constitution but also as a protector of democratic values and fundamental human rights. The findings underscore the importance of a theoretically grounded and constitutionally consistent role of the Court in reinforcing the rule of law and preventing the abuse of state power.